2009
DOI: 10.1111/j.1526-4637.2009.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain in German General Practice

Abstract: A B S T R A C TIntroduction. This study evaluates the prevalence of chronic pain, intensity of pain, activity limitation, and pain-related diagnoses in German general practices.Methods. In 40 general practices, up to 50 consecutive patients presenting to general practitioners (GP) for routine medical consultation were questioned, and those reporting pain that lasted for more than 3 months received a questionnaire referring to intensity of pain and activity limitations. GPs received a questionnaire asking about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 27 publications
1
10
0
7
Order By: Relevance
“…The characteristic of pain in our sample was similar to previous surveys with chronic pain found to be more prevalent in women and the elderly. The most common site of pain was the knees, which is consistent with a similar survey on the prevalence of chronic pain in the general population in Singapore (HDI < 0.9), although the majority of previous surveys report the back as being the most common site of chronic pain …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The characteristic of pain in our sample was similar to previous surveys with chronic pain found to be more prevalent in women and the elderly. The most common site of pain was the knees, which is consistent with a similar survey on the prevalence of chronic pain in the general population in Singapore (HDI < 0.9), although the majority of previous surveys report the back as being the most common site of chronic pain …”
Section: Discussionsupporting
confidence: 87%
“…The most common site of pain was the knees, which is consistent with a similar survey on the prevalence of chronic pain in the general population in Singapore (HDI < 0.9), 23 although the majority of previous surveys report the back as being the most common site of chronic pain. [2][3][4][5][6]27,28,32,33,34,35 We are the first to provide a preliminary estimate of the prevalence of neuropathic pain in chronic pain in Libya based on S-LANSS score of 12. Fifty percent (95% CI, 30.8% to 69.2%) of participants with chronic pain were categorized as having a neuropathic component to their pain.…”
Section: Discussionmentioning
confidence: 99%
“…Both pain phenotypes were associated with age, and the development of software which can take such covariates into account is a major advantage. We have shown for the first time that two musculoskeletal pain traits, complaints which are highly prevalent in general practice (Hensler et al, 2009) and disability adjusted for life years (Murray et al, 2012), are linked by shared genetic factors. Specifically, parameterizing CWP and LBP in a group of twins onto an unobserved continuous variable, liability scale, and accounting for the family resemblance, we showed that some 60% of the liability score variation for each of these traits is attributable to genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Für die Bundesrepublik Deutschland stehen, zumindest auf regionaler Ebene, die ersten belastbaren Daten zur Schmerzprävalenz im häus-lich-ambulanten Bereich zur Verfügung [16]. Im Bereich deutscher Hausarztpraxen zeigt sich eine Punktprävalenz von 18,6 % der Patienten, die länger als 3 Monate über Schmerzen klagen [12].…”
Section: Hintergrund Und Fragestellungunclassified